Dual inhibition of the PI3K and MAPK pathways enhances nab-paclitaxel/gemcitabine chemotherapy response in preclinical models of pancreatic cancer. (10th September 2019) - Awasthi, Niranjan; Kronenberger, David; Stefaniak, Alexis; Hassan, Md Sazzad; von Holzen, Urs; Schwarz, Margaret A.; Schwarz, Roderich E.
Abstract: Standard chemotherapy for pancreatic ductal adenocarcinoma (PDAC), nab -paclitaxel (NPT) plus gemcitabine (Gem), has led to an average survival of 8.5 months. Presently, no therapeutics exist that effectively target the KRAS oncogene, activated in 95% of PDACs, but alternative strategies focus on inhibition of downstream effectors of KRAS signaling. Through combined inhibition of PI3K and MAPK signaling with MK-2206 (MK) and trametinib (Tra), enhancement of NPT + Gem response was evaluated. Median animal survival was significantly improved by the NPT + Gem combination (67% increase). Addition of MK-2206 or trametinib further increased median survival: NPT + Gem + MK (86%), NPT + Gem + Tra (105%), and NPT + Gem + MK + Tra (129%). In cell line-derived xenografts, the net tumor growth (in mm 3 ) compared to controls (878.5) was significantly reduced by NPT + Gem (191.2), NPT + Gem + MK (150.7), NPT + Gem + Tra (62.2) and NPT + Gem + MK + Tra (49.9) therapies. In patient-derived xenografts, the combination of MK-2206 and trametinib with chemotherapy had an additive response in reducing tumor growth. Effects of therapy on tumor cell proliferation and apoptosis corresponded with tumor growth inhibition. These findings suggest that the standard chemotherapy response of PDAC can be enhanced through dual targeting of PI3K and MAPK signaling, which could lead to improved PDAC therapy. Highlights: PI3K inhibitor MK2206 and MAPK inhibitor trametinib have antitumor activity in PDAC. MK-2206 and trametinib augment animal survival benefit of nab-paclitaxel/gemcitabine. MK-2206 and trametinib enhance tumor inhibition response of nab -paclitaxel/gemcitabine. Co-targeting PI3K and MAPK signaling enhances standard chemotherapy effects of PDAC. Dual inhibition of PI3K and MAPK signaling has the potential to improve PDAC therapy.